Toxicological evaluation of porcine bile powder in Kunming mice and Sprague–Dawley rats - Wu, Lirong; Wang, Jieyi; Lei, Jing; Ge, Kun; Qu, Chun; Liu, Jiajian; Huang, Fengjie; Sun, Dongnan; Chao, Xiaowen; Chen, Tianlu; Zhao, Aihua; Jia, Wei; et al. (Frontiers in Pharmacology, 2024)
Porcine bile powder (PBP) is a traditional Chinese medicine that has been used for centuries in various therapeutic applications. However, PBP has not previously undergone comprehensive component analysis and not been evaluated for safety through standard in vivo toxicological studies. In the present study, the component of PBP were characterized and acute and subchronic oral toxicity studies of PBP were designed and conducted in Kunming mice and Sprague-Dawley (SD) rats. The chemical analysis of PBP by liquid chromatography-mass spectrometry showed that the main components of PBP were bile acids, especially glycochenodeoxycholic acid. There were no signs of toxicity observed in the acute oral test and the subchronic test. In the genotoxicity tests, no positive results were observed in the bacterial reverse mutation test. Additionally, in the mammalian micronucleus test and mouse spermatocyte chromosomal aberration test, no abnormal chromosomes were observed. In the teratogenicity test, no abnormal fetal development was observed. These results demonstrate that PBP, composed mainly of bile acids, is non-toxic and safe based on the conditions tested in this study.